2014
DOI: 10.1007/s10722-014-0205-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the molecular diversity of Olea europaea in the Mediterranean Island of Malta

Abstract: The island of Malta is a small densely populated land mass located in the middle of the Mediterranean Sea. Genetic material from local olive tree varieties on the island was amplified using RAPD, 36 loci were subsequently generated and a dendrogram based on Jaccard's similarity coefficient constructed. Analysis of clustering patterns indicated a high degree of genetic diversity (0.18-0.68), an early separation between the majority of the native varieties and more recently introduced varieties, supporting the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 4 publications
4
22
0
Order By: Relevance
“…There are three major identified olive cultivars within the Maltese islands which are thought to be native, namely the 'Bidni', 'Bajda' and 'Malti' [21]. Whilst the 'Bidni' and 'Bajda' are monocultivars, the 'Malti' is thought to be made up of several ancient varieties which are geographically isolated from each other [22]. Furthermore, recent studies have shown that Maltese EVOOs have a significantly different phenolic composition and mineral composition [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…There are three major identified olive cultivars within the Maltese islands which are thought to be native, namely the 'Bidni', 'Bajda' and 'Malti' [21]. Whilst the 'Bidni' and 'Bajda' are monocultivars, the 'Malti' is thought to be made up of several ancient varieties which are geographically isolated from each other [22]. Furthermore, recent studies have shown that Maltese EVOOs have a significantly different phenolic composition and mineral composition [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…DNA based methods are effective in allowing a traceability chain to be established between tree and oil [12]. In a first approach, random amplified polymorphic DNA (RAPD) and microsatellite analysis [11,13] were used to identify marker sequences specific to local varieties. Both studies showed that indigenous olive trees occupied a distinct group.…”
Section: Introductionmentioning
confidence: 99%
“…Syria is part of the original habitat of O. europaea , with 90 cultivars identified so far, although only five varieties, that is, Zaity, Sorani, Doebli, Khoderi, and Kaissy, are extensively cultivated ( Al-Ibrahem, Bari & Rashed, 2008 ; Tubeileh, Abdeen & Al-Ibrahem, 2008 ). In the Maltese archipelago, three principal cultivars, namely Bidnija, Maltija, and White olive or Bajda, were identified ( Mazzitelli et al, 2015 ) in addition to the rare wild olives characterized by small shrubs, short leaves, and small, bitter-tasting fruits with low oil content. The Maltija variety is highly productive and it is the most common and widespread cultivar in the islands, while Bidnija (from the Bidnija region) is believed to be one of the oldest olive cultivars, indicating that it may date back from the Roman occupation ( Buhagiar, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Maltija variety is highly productive and it is the most common and widespread cultivar in the islands, while Bidnija (from the Bidnija region) is believed to be one of the oldest olive cultivars, indicating that it may date back from the Roman occupation ( Buhagiar, 2012 ). The Bidnija produces oil of excellent quality, is rich in polyphenols and shows high tolerance to environmental stresses such as salinity and drought, and to olive fruit fly ( Mazzitelli et al, 2015 ). “Bajda” produces characteristic white drupes, and it was rediscovered in 2010, as a possible survivor of the famous Maltese “Perlina” or “Pearls of Malta” referenced in Renaissance literature ( Verde, 2017 ).…”
Section: Introductionmentioning
confidence: 99%